HUBUNGAN SIKAP BERLATIH DENGAN MOTIVASI BERLATIH TERHADAP TIM SEPAK BOLA SMAN OLAHRAGA PROVINSI RIAU - Ihza Yustrianda Imani; Aref Vai; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The purpose of this study was to determine the relationship between practice attitudes and motivation to practice for the Riau Province Senior High School Sports Team. This research was conducted at the Rumbai Da'wah Soccer Field. This research has been carried out only once on June 15, 2022. The research method used is associative (correlational). This research design consists of one independent variable and one dependent variable. The sample in this study was all of the population, namely athletes from the Riau Province Senior High School Sports Football team, which amounted to 16 people. To analyze the data used statistical techniques, data analysis used from this study using quantitative descriptive analysis techniques with percentages. Based on the results of the Attitude Practice (X) research data above, from the 16 samples there were 3 people with a score of 65-69, and 7 people scoring 69-74 people, and 1 person scoring 76 with a total of 1079 and a mean of 67.44. And from 16 people for the results of research data on motivation to practice (Y) above, from 16 samples there are 4 people with a value of 58-63, and 4 people with a value of 63-68, and 7 people with a value of 68-74 with a total of 1055 and a mean of 65.94 . Key Words: The Relationship of Practice Attitude, Motivation to Practice